2005
DOI: 10.1039/b501879j
|View full text |Cite
|
Sign up to set email alerts
|

Gull eggs—food of high organic pollutant content?

Abstract: A wide range and occasionally high levels of persistent organic pollutants (POPs) are reported in Arctic regions, especially among top predators. Polar bears (Ursus maritimus), arctic foxes (Alopex lagopus) and some gull species (Larus spp.) often have high levels of these fat-soluble pollutants. Gulls deposit significant levels of these contaminants in their eggs. In northern regions, gull eggs are part of the traditional human diet. In the present study we have investigated the levels of POPs in gull eggs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…A study on predatory birds from the UK in 2014 however, reported concentrations of PCB levels below the limit of detection to 248 pg WHO TEQ/g lw, while not detecting PCB126 in any of the samples (Pereira et al, 2014). In herring gull eggs from the north of Norway, average levels of 65.5 pg WHO TEQ/ g ww were measured (Pusch et al, 2005), and on Northern Norwegian islands, four PCB congeners with WHO TEF values (PCB105,118,156,157), were measured in herring gull eggs, with values of between 45 and 83 pg WHO TEQ/g lw (Helgason et al, 2008), while in the current study the WHO TEQ (sum of PCB105, 118, 156, 157) accounts for 9-36 pg/g lw. To summarize, the TEQ levels in the current study are up to an order of magnitude lower than eggs from the USA and a factor of between 2 and 5 times lower than herring gull eggs from Norway in studies from 2002 and 2005.…”
Section: Resultsmentioning
confidence: 96%
“…A study on predatory birds from the UK in 2014 however, reported concentrations of PCB levels below the limit of detection to 248 pg WHO TEQ/g lw, while not detecting PCB126 in any of the samples (Pereira et al, 2014). In herring gull eggs from the north of Norway, average levels of 65.5 pg WHO TEQ/ g ww were measured (Pusch et al, 2005), and on Northern Norwegian islands, four PCB congeners with WHO TEF values (PCB105,118,156,157), were measured in herring gull eggs, with values of between 45 and 83 pg WHO TEQ/g lw (Helgason et al, 2008), while in the current study the WHO TEQ (sum of PCB105, 118, 156, 157) accounts for 9-36 pg/g lw. To summarize, the TEQ levels in the current study are up to an order of magnitude lower than eggs from the USA and a factor of between 2 and 5 times lower than herring gull eggs from Norway in studies from 2002 and 2005.…”
Section: Resultsmentioning
confidence: 96%
“…Due to its high trophic position in the food web, the herring gull accumulates high levels of HOCs [19].…”
Section: Model Speciesmentioning
confidence: 99%
“…The data derived (2000) from classical chemical monitoring are used to assess status and trends with respect to water chemistry, eutrophication, hazardous substances and phycotoxins. The components investigated cover water, sediment and biota (primarily fish and shellfish, but also marine mammals (Pierce et al ., 2008;Law et al ., 2010), seabird eggs (Becker, 1989;Pusch et al ., 2005) and seaweed (Caliceti et al ., 2002)), while the techniques incorporate methods that allow normalization of data as well as those that produce concentrations of compound X in component Y. Sample preparation (extraction/isolation of the analyte and associated clean-up) is, for some methodologies, relatively simple.…”
Section: Some Considerations Around Classical Chemical Monitoring Andmentioning
confidence: 99%